2010
DOI: 10.1111/j.1524-4725.2009.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Study of Normal, Ingrown, and Pincer Nails

Abstract: The findings suggest that the mechanical cause may be associated with the over curved nail, which is affected by nail bed contraction. Results may support the hypothesis that an osteophyte of the distal phalanx may not be a cause of, but rather a result of, an overcurving deformity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 16 publications
0
36
0
19
Order By: Relevance
“…It is reported that the pincer nails tend to show a greater inward curvature on the distal side [18]. The same portions of the nail are converted in koilonychia [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the pincer nails tend to show a greater inward curvature on the distal side [18]. The same portions of the nail are converted in koilonychia [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, however, suggest that an osteophyte of the distal phalanx is not a cause of but rather a result of a nail overcurvature. 2,12 They hypothesize that the physical difference between the ventral and dorsal sides of the nail plate is the cause of a pincer nail, and the harder dorsal nail plate causes the plastic ventral nail plate to be contracted, resulting in nail bed shrinkage or constriction. 9 Although several conservative and surgical treatment options have been introduced to correct pincer nails, there is no standardized method for achieving rapid improvement, low recurrence, and cosmetically appealing results.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] To correct pincer nail deformities, several conservative and surgical treatment methods have been suggested, with limited success. As of yet, there is no established standard method for treating pincer nail deformity.…”
mentioning
confidence: 99%
“…As in a number of other studies, 5 the authors mention the secondary traction osteophytes but fail to report the widening of the base of the distal phalanx. This is often seen as hook-like osteophytes, which are much more pronounced medially than laterally and are probably the reason for the pronounced lateral deviation of the overcurved big toenail.…”
mentioning
confidence: 82%